The Place of Murassa Hardcover Mushafs in Decoration - KARADENİZ, Yıldırım (MAS Journal of Applied Sciences, 2023)
Murassa is a type of binding with high material value, which is generally applied to the bindings of the Qur’an, together with the art of bookbinding and the art of jewellery. Murassa binder, the desire to reproduce and preserve the Qur’an in the regions where Islam spread, led to the development of bookbinding as an important branch of art. There are motifs and arrangements that reflect the unique taste of each period and region. One of the centers in the Islamic world where quality bindings are produced is Istanbul, the capital of the Ottoman Empire. On the other hand, original and distinguished examples of Islamic bookbinding were produced during the Timurids, Akkoyunlu Turkmens, Safavids, and Mamluks in Egypt. The bookbinding art, which passed from Central Asia to Iran, the Arabian Continent and Anatolia, was adorned with the motifs of the regions where the artists grew up, and various binding styles were formed with Arabesque, Herat, Hatai, Rumi Seljuk, Mamluk, Ottoman and Moorish motifs. During the Ottoman Empire; "Murassa" manuscripts, which were produced with superior jewelery techniques, especially in the period between the 16th and 19th centuries, are exhibited in many Museums and Libraries at home and abroad today. In this article; The "murassa" artifacts belonging to the Ottoman Period, which are found in the Topkapı Palace Museum and determined as a result of literature research, will be examined in detail in terms of the decoration features of the period they belong to; will be discussed in terms of composition, pattern, material, technique and motif features, and its place and evaluation in bookbinding art will be made.